2015
DOI: 10.1002/jssc.201500303
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantitation of major phenolic compounds from penthorum chinense pursh. by HPLC with tandem mass spectrometry and HPLC with diode array detection

Abstract: Penthorum chinense Pursh. is a traditional Chinese herbal medicine used for the treatment of various ailments specially related to liver. Gansu Granule, the medicine made from the extract of P. chinense, has been widely used in the clinical setting. But the information about its active ingredients is lacking. In this paper, the extract of P. chinense was analyzed by high performance liquid chromatography with electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry. Among the 27 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…,6″-(s)-HHDP]-β-D-glucose, and Thonningianin A, respectively. 23,33 The characteristic fragments of compounds S1, S2, and S3 (m/z 301) indicated the lost pinocembrin residue ( Figure 2).…”
Section: Pinocembrin Derivatives Preparation and Identificationmentioning
confidence: 99%
“…,6″-(s)-HHDP]-β-D-glucose, and Thonningianin A, respectively. 23,33 The characteristic fragments of compounds S1, S2, and S3 (m/z 301) indicated the lost pinocembrin residue ( Figure 2).…”
Section: Pinocembrin Derivatives Preparation and Identificationmentioning
confidence: 99%
“…This compound fragmented with the loss of glucose to pinostrobin ( m / z 271.09 [M + H − 162] + ) which further fragmented with a neutral loss of 104 Da to m / z 167.04 [M + H − 162–104] + . The likely structures of these compounds are pinocembrin-7- O -glucoside and 5-methoxy-pinocembrin-7- O -glucoside ( Fig 5 ), which have been shown to co-occur in aerial parts of Penthorum chinense (Penthoraceae; [ 45 ]). Moreover, both compounds have been found individually in many different plant families, but not previously in Myrtaceae.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids are common active components in herbs, which show a variety of biological activities, including not only antioxidation but also bacteriostatic effects [32] . Previous studies reported that quercetin and pinocembrin-7-O-β-glucoside [33][34][35] are abundant in PCP. Both compounds showed antibacterial activity [36,37] .…”
Section: Discussionmentioning
confidence: 99%